O uso do Graxaim/LVT nos estudos de recuperação paralela no ensino de física para o ensino médio - Porto, Luiz Eduardo Silva (2018)
In this dissertation, we present a work proposal - based on Information and Communication Technologies (TIC) - for parallel recovery studies (RP) in the contents of thermodynamics in Integrated High School regularly offered at the Farroupilha Federal Institute, Panambi campus (IFFar). This work arises from a classroom demand of the author of this text, which acts as regent teacher at IFFar and is related to aspects of didactic practice in physics classes and in PR studies. In this sense, we seek to reflect on our own practice in search of transformation and improvement. We present a set of didactic activities (AD) to be tested in RP studies, using the Graxaim/Virtual Laboratory of Thermodynamics (Graxaim/LVT) as a computational didactic resource. The AD set was tested in the period from May to November 2017 in classes where the author is a regent teacher. We sought to understand the potential of a didactic resource in physics classes and to analyze the Graxaim/LVT as a resource to be incorporated into regular physics classes. From the analysis of the class diaries and a questionnaire applied at the end of this work, we perceived a greater adherence and permanence in the studies of RP besides expanding the spaces of study of the students with a AD with a greater potential of challenge than the traditional expositive classes. Also, we perceive an improvement in students' understanding of PR studies. A next step involves experimenting with other cycles or sub-cycles of this work in the light of the Educational Design Research (EDR) research conception in search of the enhanced learning with the experimentation of Graxaim/LVT as didactic resource.